A systematic literature review of nutrition interventions in vending machines that encourage consumers to make healthier choices. Issue 12 (10th September 2015) - Grech, A.; Allman‐Farinelli, M.
Summary: Internationally, vending machines are scrutinized for selling energy‐dense nutrient‐poor foods and beverages, and the contribution to overconsumption and subsequent risk of obesity. The aim of this review is to determine the efficacy of nutrition interventions in vending machine in eliciting behaviour change to improve diet quality or weight status of consumers. Electronic databases Cochrane, EMBASE, CINAHL, Science Direct and PubMed were searched from inception. Inclusion criteria: (i) populations that have access to vending machines; (ii) nutrition interventions; (iii) measured outcomes of behaviour change (e.g. sales data, dietary intake or weight change); and (iv) experimental trials where controls were not exposed to the intervention. Risk of bias was assessed independently by two researchers, and higher quality research formed the basis of this qualitative review. Twelve articles from 136 searched were included for synthesis. Intervention settings included schools, universities and workplaces. Reducing price or increasing the availability increased sales of healthier choices. The results of point‐of‐purchase nutrition information interventions were heterogeneous and when measured changes to purchases were small. This review offers evidence that pricing and availability strategies are effective at improving the nutritional quality foods and beverages purchased from vending machines. Evidence on how these interventions alter consumer's overall diet or body mass index is needed.